2013
DOI: 10.1111/jocn.12368
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and the prevention of breast cancer: a retrospective review of clinical histories

Abstract: Nurses play a crucial role in encouraging new mothers to breastfeed their children, and this helps to prevent breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 33 publications
0
24
0
3
Order By: Relevance
“…Risk reduction for breast cancers after several deliveries and breast-feeding periods has been described for several decades (reviewed in Refs. [15][16][17][18][19][20][21][22][23]. Some of these studies reported that increased parity also reduced the risk for endometrial and ovarian cancers.…”
Section: Breast Cancer Risk Of Multiparous Womenmentioning
confidence: 99%
“…Risk reduction for breast cancers after several deliveries and breast-feeding periods has been described for several decades (reviewed in Refs. [15][16][17][18][19][20][21][22][23]. Some of these studies reported that increased parity also reduced the risk for endometrial and ovarian cancers.…”
Section: Breast Cancer Risk Of Multiparous Womenmentioning
confidence: 99%
“…The benefits for the infant include a diminished risk of infectious diseases and obesity and decreased blood pressure (Brion et al, 2011;Duijts et al, 2010;Horta et al, 2007). For the mother, breastfeeding confers a lower risk of ovarian and breast cancers and decreased blood pressure (Ebina and Kashiwakura, 2012;González-Jiménez et al, 2013;Jonas et al, 2008). Recognized as the optimal infant feeding method, the guidelines specified by the World Health Organization (WHO), the European Commission for Public Health (ECPH) and the American Academy of Pediatrics (AAP) recommend exclusive breastfeeding in the first 6 months postpartum (American Academy of Pediatrics, 2012; EU Project on Promotion of Breastfeeding in Europe, 2008;World Health Organization, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…La lactancia materna presenta un impacto positivo con los Objetivos de Desarrollo del Milenio (ODM) al reducir la mortalidad infantil [16] y mejorando la salud materna gracias a la protección contra enfermedades crónicas [17][18][19][20].…”
Section: Introductionunclassified